Nox Emission Characteristics of Steam Addition on Marine Diesel Engine Fueled with Various Blended Palm Oil Methyl Ester - Sheikh Alif Ali (Universiti Malaysia Terengganu, 2023)
Ships transport enormous quantities of essential goods through the world's oceans and emit high and varying quantities of nitrogen oxides (Nox), which are detrimental to the environment. The oxidation of organic fuels in a clean and safe manner is critical to human activity.